Implementation of a re‐linkage to care strategy in patients with chronic hepatitis C who were lost to follow‐up in Latin America. Issue 1 (17th October 2022) - Mendizabal, Manuel; Thompson, Marcos; Gonzalez‐Ballerga, Esteban; Anders, Margarita; Castro‐Narro, Graciela E.; Pessoa, Mario G.; Cheinquer, Hugo; Mezzano, Gabriel; Palazzo, Ana; Ridruejo, Ezequiel; Descalzi, Valeria; Velarde‐Ruiz Velasco, Jose A.; et al.
Abstract: To achieve WHO's goal of eliminating hepatitis C virus (HCV), innovative strategies must be designed to diagnose and treat more patients. Therefore, we aimed to describe an implementation strategy to identify patients with HCV who were lost to follow‐up (LTFU) and offer them re‐linkage to HCV care. We conducted an implementation study utilizing a strategy to contact patients with HCV who were not under regular follow‐up in 13 countries from Latin America. Patients with HCV were identified by the international classification of diseases (ICD‐9/10) or equivalent. Medical records were then reviewed to confirm the diagnosis of chronic HCV infection defined by anti‐HCV+ and detectable HCV‐RNA. Identified patients who were not under follow‐up by a liver specialist were contacted by telephone or email, and offered a medical reevaluation. A total of 10, 364 patients were classified to have HCV. After reviewing their medical charts, 1349 (13%) had undetectable HCV‐RNA or were wrongly coded. Overall, 9015 (86.9%) individuals were identified with chronic HCV infection. A total of 5096 (56.5%) patients were under routine HCV care and 3919 (43.5%) had been LTFU. We were able to contact 1617 (41.3%) of the 3919 patients who were LTFU at the primary medical institution, of which 427 (26.4%) were cured at a different institutions or were dead. Of the remaining patients, 906 (76.1%) were candidates for retrieval. In our cohort, about one out of four patients with chronic HCV who were LTFU were candidates to receive treatment. This strategy has the potential to be effective, accessible and significantly impacts on the HCV care cascade.